2020
DOI: 10.2991/artres.k.200819.001
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity Comparing Estimated and Direct Measures of Path Length in Older Women

Abstract: Background: Carotid-femoral Pulse Wave Velocity (cfPWV) is the gold-standard measure of arterial stiffness. Accuracy of non-invasive cfPWV as meters per second is impeded by surface estimates of aortic length. Our aim was to compare cfPWV measured using distance estimated from surface measurements with distance traced along the length of the aorta using Magnetic Resonance Imaging (MRI) in a cohort of older women.Methods: Seventy-four women were recruited from the TwinsUK cohort. cfPWV was measured using the Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This is also reflected in the lower damping index found by the authors between those vascular segments (1.31 ± 0.30 vs. 2.1 ± 0.81 in this study). The proximal measures of pressure and arterial stiffness assessed in this study were similar to those reported in the literature 19,22–25 . Slight differences were likely due to the fact that we included participants with variable levels of risk factors and vascular events, which assured us of the required variation in the measures of proximal pressure and arterial stiffness.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This is also reflected in the lower damping index found by the authors between those vascular segments (1.31 ± 0.30 vs. 2.1 ± 0.81 in this study). The proximal measures of pressure and arterial stiffness assessed in this study were similar to those reported in the literature 19,22–25 . Slight differences were likely due to the fact that we included participants with variable levels of risk factors and vascular events, which assured us of the required variation in the measures of proximal pressure and arterial stiffness.…”
Section: Discussionsupporting
confidence: 61%
“…The proximal measures of pressure and arterial stiffness assessed in this study were similar to those reported in the literature. 19 , 22 , 23 , 24 , 25 Slight differences were likely due to the fact that we included participants with variable levels of risk factors and vascular events, which assured us of the required variation in the measures of proximal pressure and arterial stiffness. In case of too little variation in the measurements, observed variability would only be noise and not contain information from which relations can be inferred.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was corroborated by Weir-McCall et al (2017), who noted that cfPWV was approximately 30% higher than MRI-PWV in a diverse group of elderly individuals. In a similar manner, Ludovica et al (2020) reported that cfPWV was roughly 17% higher than MRI-PWV in a cohort of elderly females (Weir-McCall et al, 2017;Ludovica et al, 2020). Podolec et al (2007) discovered that regional cfPWV was approximately 28% higher than local aortic PWV, which was recorded as 7.4 m/s in a group of middle-aged to elderly individuals diagnosed with stable angina but without coronary artery stenosis (Podolec et al, 2007).…”
Section: Parameter Identification Process Generated Pwv Compared To C...mentioning
confidence: 78%